Classficational Study of Parasitic Chewing Lice types on domestic and wild pigeon in Al-Diwaniya city - Hamza Al-Mayali, Hadi Madlul; Alwan Al-Shabany, Marwa Sami (Al-Qadisiyah Journal of Pure Science, 2018)
In this study we collected the samples during the period from November 2011 to October 2012 240 of Columba livia ,240 samples of Columba domestica of Al-Dywania city, 20 samples for every type of the studied birds monthly.This is to discover the parasitic lice types in these birds and diagnosis them.In addition to testify the proportion and intensity of the infection of those parasites.The results showed that C.livia and C.domestica were infested with seven species of chewing lice they are :Columbicola columbae in C.livia and C.domestica with the intensity of infection (2.08,14.58% ; 2.14,8.75%)respectively ,Columbicola tschulyschman in C.livia and C.domestica with the intensity of infection (1.12,10% ; 1.58,7.08%)respectively ,Campanulotes compare in C.livia and C.domestica with the intensity of infection (1.2,8.33% ; 2.42,16.66%)respectively ,Colocerasdamicorne in C.livia and C.domestica with the intensity of infection (1.14,5.83% ; 1.53,5.41%) respectively ,Bonomiella columbae in C.livia and C.domestica with the intensity of infection (2.4,2.08% ; 1.25,1.66%) respectively ,Hohorstiella lata in C.livia and C.domestica with the intensity of infection (1.27,4.58% ; 1.75,1.66%) respectively ,Menacanthusstramineus in C.domestica with the intensity of infection (1.28,2.9%)respectively .Results showed that single infection of lice in C.livia and C.domestica are the most common to 54.32% and 51.32% respectively .Results also showed that there is no difference between males C.livia and C.domestica and females in readiness to get infection with lice. No differences were found between the different weight groups in percentage infection with lice.